IoT Based Multi-Node Health Monitoring System - Rupali Bhandwaldar, Devendra Bhuyar, Dr. Kureshi A. K (International Journal of Advanced Science and Technology, 2020)
In the last few years, tremendous technology revolution has been observed in the medical industry concerning real-time health monitoring applications utilizing the Internet of Things (IoT). Low power sensor node design with reliable and low delay in communication has paramount importance for such applications. In this research paper, we have come up with a design of reliable, low power and cost-effective multi-node health monitoring system. The proposed system uses multiple nodes connected using star topology. All the on-body sensors with a microcontroller constitute a node. Patient health can be monitored using varied parameters. The node in the proposed system measures health parameters that include body temperature, Electrocardiography (ECG), blood pressure and heart rate. An IRD (InfraRed Device sensor) is utilized to estimate the patient pulse count. The device uses an optical LED light source and an LED light sensor, which can be conveniently mounted on a thumb finger to give continuous pulses. The temperature of a patient is monitored using a highly sensitive temperature sensor. ECG module is used to measure the patient’s ECG. With the help of these sensor devices, a patient’s health is inspected and collected data is transferred to the monitoring station. RF communication is utilized to transfer the data to the monitoring station. This data is also transferred to a website by interfacing an IoT module to a controller on a node. The proposed solution can be used to effectively monitor the multiple patients in a hospital ward as well as remotely located patients which will ultimately reduce hospital operating costs and improving the quality of health service.